Podophyllotoxin and Rutin Modulates Ionizing Radiation-Induced Oxidative Stress and Apoptotic Cell Death in Mice Bone Marrow and Spleen - Singh, Abhinav; Yashavarddhan, M. H.; Kalita, Bhargab; Ranjan, Rajiv; Bajaj, Sania; Prakash, Hridayesh; Gupta, Manju Lata (Frontiers in Immunology, 2017)
The present study is aimed to investigate the radioprotective efficacy of G-003M (combination of podophyllotoxin and rutin) against gamma radiation-induced oxidative stress and subsequent cell death in mice bone marrow and spleen. Prophylactic administration of G-003M (−1 h) rendered more than 85% survival in mice exposed to 9 Gy (lethal dose) with dose reduction factor of 1.26. G-003M pretreated mice demonstrated significantly reduced level of reactive oxygen species, membrane lipid peroxidation, and retained glutathione level. In the same group, we obtained increased expression of master redox regulator, nuclear factor erythroid-derived like-2 factor (Nrf-2), and its downstream targets (heme oxygenase-1, Nqo-1, glutathione S-transferase, and thioredoxin reductase-1). In addition, G-003M preadministration has also shown a significant reduction in Keap-1 level (Nrf-2 inhibitor). Radiation-induced lethality was significantly amended in combination-treated (G-003M) mice as demonstrated by reduced 8-OHdG, annexin V FITC+ cells, and restored mitochondrial membrane potential. Expression of antiapoptotic protein Bcl-2 and Bcl-xL was restored in G-003M pretreated group. However, proapoptotic proteins (Puma, Bax, Bak, Caspase-3, and Caspase-7) were significantly declined in this group. Further analysis of immune cells revealed G-003M-mediated restoration of CD3 and CD19 receptor, which was found decreased to significant level following irradiation. Similarly, Gr-1, a marker of granulocytes, was also retained by G-003M administration prior to radiation. Modulatory potential of this formulation (G-003M) can be exploited as a safe and effective countermeasure against radiation-induced lymphohemopoietic injury.